OVERGROUND WALKING ALONG WITH COUNTING BACKWARDS INFLUENCES MOVEMENT VARIABILITY IN HEALTHY YOUNG AND OLDER ADULTS - Soangra, Rahul; Lockhart, Thurmon E (Biomedical sciences instrumentation, 2017)
Performance of secondary task i.e. dual task affects certain aspects of gait, but the relationship between gait variability and dual tasking is not well understood. This study evaluated the effects of the dual-task paradigm on measures of movement variability changes in two healthy age groups. Seven young (age 22.6±2.5 years, height 170.3±9.3 cm and weight 69.6±15.5 Kgs) and seven old participants (age 71.14±6.5 years, height 174.5±10.2 cm and weight 78.5±18.2 Kgs) were recruited for this study. Since cognitive task such as mental arithmetic tasks (for example counting backwards by subtracting three digits) are self-generated, and are performed with selected spontaneous rhythm, so are used as secondary task while walking. An inertial measurement unit was affixed at sternum level and anterior-posterior angular velocities were used for determining stride intervals and peak accelerations during each stride. It was found that healthy older adults have significantly higher dynamic stability (p<0.01) and we also found that dual-tasking significantly increases complexity in stride interval time signals in both young and older adults (p=0.01). In conclusion the findings of this study elucidate that dual-task related changes in gait compensate with movement variability but may not predispose healthy young and older adults to falls.